The concept of generosity in Rumi's Mathnawi : an analysis - Suzana Suhailawaty Md. Sidek (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2015)
This work examines generosity in the Mathnawi of Maulana Rumi. The thesis identifies fifteen stories not related directly to generosity in the Mathnawi. These were categorized into three groups: acts which are devoid of any generosity, sincere generosity, insincere generosity. These are mainly stories involving companions, saints and sometimes fables. The stories pertaining to the Prophet were used differently by Rumi. In some instances, he changed the gender of the person from that in the hadith and embellishes the stories with his own story. There are instances in which he takes two separate hadiths and make them one. In all cases, Rumi changes the scenario to make his own. The extensive change to the original does not allow us to call them hadith anymore. This dissertation shows that Rumi has spared no opportunity to show that generosity is extremely important in all its form and without being generous, one cannot reach the highest station in life. This is because the thesis shows that in Islam it does not only involve giving, but giving the best we have.